Optimization of information technology utilization based on geography information system as a marketing media for micro, small, and medium enterprises to improve competitiveness in Bantul Regency, Indonesia - Hardiyanto, Denny; Sholeh, Muhammad; Rachmawati, Rr Yuliana (IOP conference series. Materials Science and Engineering, 2020)
Micro, small and medium enterprises (MSMEs) are the largest group of economic actors in the Indonesian economy. The growth of the micro industry grew by 8% every year, especially in Bantul Regency, Special Region of Yogyakarta. Various factors that led to the growth of the small micro industry in Bantul were caused by the increasing stretch of business in the creative economy sector, the majority of which were engaged in the craft sector. As support, the Government of Bantul provides policies that protect or secure raw materials for handicraft or industrial production properly and facilitate physical promotion by participating in various exhibition events through online media. In the era of information technology development, the support of online information system become one of the promotional media that can reach a large area. The research objectives are to build a website for MSME in Bantul Regency and to provide a media for MSME actors to advertise their goods and services. In this study, the MSME information system that was built was equipped with facilities for maps, images and videos of MSME products. This map facility makes it easy for users to go to business locations. The system was developed by utilizing the Application Programming Interface (API) of google map and database used to store all MSME data using MySQL with the PHP: Hypertext Pre-processor Programming language. The result is development of marketplace website (https://wartacara.com/ukm) that have many features to explore and advertise MSME actor in Bantul Regency.